2015
DOI: 10.1017/s0007485315000358
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding implicates 23 species and four orders as potential pollinators of Chinese knotweed (Persicaria chinensis) in Peninsular Malaysia

Abstract: Chinese knotweed (Persicaria chinensis) is of ecological and economic importance as a high-risk invasive species and a traditional medicinal herb. However, the insects associated with P. chinensis pollination have received scant attention. As a widespread invasive plant we would expect P. chinensis to be associated with a diverse group of insect pollinators, but lack of taxonomic identification capacity is an impediment to confirm this expectation. In the present study we aimed to elucidate the insect pollinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…91.0% of OTU were assigned an order name. Due to incompleteness of DNA barcode reference libraries available for the region (Wong et al , 2015; Wilson et al , 2016), we did not systematically assign more precise taxonomic names to the OTU.…”
Section: Methodsmentioning
confidence: 99%
“…91.0% of OTU were assigned an order name. Due to incompleteness of DNA barcode reference libraries available for the region (Wong et al , 2015; Wilson et al , 2016), we did not systematically assign more precise taxonomic names to the OTU.…”
Section: Methodsmentioning
confidence: 99%
“…1). Consequently, we used the program Primer3 Plus (Rozen & Skaletsky, 2000) and a set of diverse high-quality insect COI sequences from another study (Wong et al, 2015) to select a 22 bp region slightly downstream of MLepF1 with appropriate structural and physical properties for primer binding. We included two degenerate bases (Ws) to create a reverse version of MLepF1 (named MLepF1-Rev).…”
Section: Primer Selection and Testing: Individual Specimenmentioning
confidence: 99%
“…There is a gap in the understanding of the seed ecology of Chinese knotweed in Aotearoa / New Zealand. Studies overseas have indicated the flowers are insect pollinated (Wong et al 2015), and the seeds are dispersed by animals (Partasasmita & Ueda 2005). Seed dormancy triggers and germination conditions for this species are unknown, however closely related species have been studied internationally (Smith et al 2014;Justice 1941;Timson 1965).…”
Section: Introductionmentioning
confidence: 99%